Effects of Nitrogen Addition and Reproductive Effort on Nutrient Resorption of a Sand-Fixing Shrub - Wang, Lilong; Li, Yulin; Duan, Yulong; Lian, Jie; Luo, Yongqing; Wang, Xuyang; Luo, Yayong (Frontiers in Plant Science, 2020)
Caragana microphylla is a sand-fixing leguminous shrub with strong resistance to drought, cold, and low soil fertility. As a result, it plays an essential role in combating desertification in northern China, but little is known about its nutrient budget. Nutrient resorption is a key process in plant nutrient conservation and has marked ecological implications for plant fitness and ecosystem nutrient cycling. We studied the effects of both nitrogen (N) addition and reproductive effort on leaf N resorption of C. microphylla in a temperate semi-arid sandy land in China. The results showed that sprouting of the early leaves from over-wintered buds employs a strategy for slow returns on nutrient investment with smaller specific leaf area (SLA) and higher N resorption efficiency, whereas the late leaves, which sprout from current-year buds, employ a strategy for quick returns on nutrient investment with higher SLA and lower N resorption efficiency. N addition significantly increased the N resorption efficiency from early leaves while exerting no impact on late leaves, suggesting that the increased N recovery from early leaves is done to sustain the high N demands of late leaves. Reproductive effort did not affect the N resorption from early or late leaves due to the temporal separation between fruit production and leaf senescence. Taken together, our results demonstrate that C. microphylla has evolved different investment strategies for leaf N in early and late leaves to conserve nutrients and facilitate its growth in desertified environments.